3-Bromo-4,5-dihydroxybenzaldehyde Protects Keratinocytes from Particulate Matter 2.5-Induced Damages - Ao-Xuan Zhen; Mei-Jing Piao; Kyoung-Ah Kang; Pincha-; Herath-Mudiyan; Suk-Ju Cho; Jin-Won Hyun (MDPI AG, 2023)
Cellular senescence can be activated by several stimuli, including ultraviolet radiation and air pollutants. This study aimed to evaluate the protective effect of marine algae compound 3-bromo-4,5-dihydroxybenzaldehyde (3-BDB) on particulate matter 2.5 (PM2.5)-induced skin cell damage in vitro and in vivo. The human HaCaT keratinocyte was pre-treated with 3-BDB and then with PM2.5. PM2.5-induced reactive oxygen species (ROS) generation, lipid peroxidation, mitochondrial dysfunction, DNA damage, cell cycle arrest, apoptotic protein expression, and cellular senescence were measured using confocal microscopy, flow cytometry, and Western blot. The present study exhibited PM2.5-generated ROS, DNA damage, inflammation, and senescence. However, 3-BDB ameliorated PM2.5-induced ROS generation, mitochondria dysfunction, and DNA damage. Furthermore, 3-BDB reversed the PM2.5-induced cell cycle arrest and apoptosis, reduced cellular inflammation, and mitigated cellular senescence in vitro and in vivo. Moreover, the mitogen-activated protein kinase signaling pathway and activator protein 1 activated by PM2.5 were inhibited by 3-BDB. Thus, 3-BDB suppressed skin damage induced by PM2.5.